2022
DOI: 10.3390/plants11030254
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Domain Protein Kinase PiCDPK1 Regulates Pollen Tube Growth Polarity through Interaction with RhoGDI

Abstract: The pollen-specific calcium-dependent protein kinase PiCDPK1 of Petunia inflata has previously been shown to regulate polarity in tip growth in pollen tubes. Here we report the identification of a Rho Guanine Dissociation Inhibitor (PiRhoGDI1) as a PiCDPK1 interacting protein. We demonstrate that PiRhoGDI1 and PiCDPK1 interact in a yeast 2-hybrid assay, as well as in an in vitro pull-down assay, and that PiRhoGDI1 is phosphorylated by PiCDPK1 in vitro. We further demonstrate the PiRhoGDI1 is capable of rescuin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Overexpression of PiCDPK1 induced extremely short pollen tubes with almost spherical tips, resembling those caused by ROP overexpression ( Yoon et al., 2006 ; Scheible et al., 2022 ). Co-expression of PiGDI1 suppressed the depolarized pollen tube growth caused by excess PiCDPK1 , suggesting that PiCDPK1 negatively regulates GDI1 by phosphorylation ( Scheible et al., 2022 ). Although a similar mechanism has not been reported in Arabidopsis , CPK3, a calcium-dependent protein kinase, regulates the development of leaf pavement cells by phosphorylating GDI1 in Arabidopsis ( Wu et al., 2013 ).…”
Section: Regulators Of the Regulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of PiCDPK1 induced extremely short pollen tubes with almost spherical tips, resembling those caused by ROP overexpression ( Yoon et al., 2006 ; Scheible et al., 2022 ). Co-expression of PiGDI1 suppressed the depolarized pollen tube growth caused by excess PiCDPK1 , suggesting that PiCDPK1 negatively regulates GDI1 by phosphorylation ( Scheible et al., 2022 ). Although a similar mechanism has not been reported in Arabidopsis , CPK3, a calcium-dependent protein kinase, regulates the development of leaf pavement cells by phosphorylating GDI1 in Arabidopsis ( Wu et al., 2013 ).…”
Section: Regulators Of the Regulatorsmentioning
confidence: 99%
“…Phosphorylation may also influence the activity of GDIs. A study in Petunia inflata indicated that PiCDPK1, a pollen-specific calcium-dependent protein kinase, interacted with and phosphorylated PiGDI1 ( Figure 1 ) ( Scheible et al., 2022 ). Overexpression of PiCDPK1 induced extremely short pollen tubes with almost spherical tips, resembling those caused by ROP overexpression ( Yoon et al., 2006 ; Scheible et al., 2022 ).…”
Section: Regulators Of the Regulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two CDPKs were identified in Petunia pollen, and one was shown to modulate the polar extension of the tube because its over-expression resulted in swollen spherical tubes [10]. Evidence suggests that this kinase, PiCPDPK1, interacts with a rho guanine dissociation inhibitor (RhoGDI), a negative regulator of Rho GTPase activity, as their co-expression rescues the CDPK over-expression phenotype [11]. Rho GTPase activity is a well-characterized regulator of polar pollen tube growth in Arabidopsis [12].…”
Section: Introductionmentioning
confidence: 99%
“…are elucidated. This group includes articles [1,2,7,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], communications [27,28], and review papers [5,6,11,[29][30][31][32][33][34] with significant results applicable both in science and practice. The biology and ecology of plant secondary metabolites, their identification, and biological and therapeutic activity from different aspects of the phytochemistry of edible, aromatic, medicinal, or potentially medicinal plants are represented in a significant number of articles [3,8,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], as well as review papers [9,50,<...…”
mentioning
confidence: 99%